Editorial - Ismail, Al Emran; Ibrahim, Nabilah; Daud, Zawawi (International Journal of Integrated Engineering, 2018)
This special issue of International Journal of Integrated Engineering provides deep research on Mechanical Engineering, contains 30 papers contributions by more than 50 authors from various institutions. Theses papers are selected from three occasions held in 2018 such as International Conference on Mechanical and Manufacturing Engineering (ICME2018), Symposium on Damage Mechanisms in Materials and Structures (SDMMS2018) and International Conference and Symposium on Occupational Safety and Health (ISOSH2018). This special appreciation goes to all Editorial Team members and also Guest Editorial Team members for the evaluation process with strict comments to improve the quality of the content.